2019
DOI: 10.1002/chem.201901460
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress on the Design, Characterization, and Application of Superalkalis

Abstract: Superalkalis are clusters or molecules featuring lower ionization energies (IEs) than that of cesium atoms, and thus exhibit excellent reducing properties. Such special species have great potential to be used in the synthesis of unusual charge‐transfer salts and cluster‐assembled nanomaterials with tailored properties, in the reduction of carbon dioxide, or as hydrogen storage materials and noble‐gas‐trapping agents, etc. In this regard, ongoing efforts have been devoted to designing and characterizing superal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 198 publications
(226 reference statements)
0
38
0
Order By: Relevance
“…According to the initial definition of superalkalis, 32 these species are characterized by their lower IE 1 than those of alkali metal atoms. Some authors 33 use a more rigorous definition that only the species with IEs below the threshold of the atomic IE 1 (Cs) = 3.89 eV can be classified as superalkalis. Nevertheless, in this paper, the species with IE 1 lower than constitutive alkali atom, that is, Li (5.39 eV) were considered as superalkalis.…”
Section: Resultsmentioning
confidence: 99%
“…According to the initial definition of superalkalis, 32 these species are characterized by their lower IE 1 than those of alkali metal atoms. Some authors 33 use a more rigorous definition that only the species with IEs below the threshold of the atomic IE 1 (Cs) = 3.89 eV can be classified as superalkalis. Nevertheless, in this paper, the species with IE 1 lower than constitutive alkali atom, that is, Li (5.39 eV) were considered as superalkalis.…”
Section: Resultsmentioning
confidence: 99%
“…In ML k +1 , one more alkali metal atom will bring an extra valence electron for the electronic shell of M according to the octet rule. Consequently, such an ML k +1 complex has a great tendency to lose the extra valence electron and thus possess strong reducibility ( Sun and Wu, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…In view of the great importance of superalkalis in chemistry, various superalkalis have been theoretically ( Tong et al, 2009 ; Tong et al, 2011 , Tong et al, 2012a , Tong et al, 2012b ; Hou et al, 2013 ; Liu et al, 2014 ; Sun et al, 2013 ; Sun et al, 2016a ; Giri et al, 2016 ; Zhao et al, 2017 ; Sun et al, 2018b ; Sun et al, 2019 ; Park and Meloni, 2018 ; Sun and Wu, 2019 ; Tkachenko et al, 2019 ; Sikorska and Gaston, 2020 ) and experimentally ( Lievens et al, 1999 ; Yokoyama et al, 2000 , 2001 ; Hou and Wang, 2020 ) characterized in the past decades. To date, conventional mononuclear ML k +1 superalkalis have been expanded to dinuclear ( Tong et al, 2009 ; Tong et al, 2011 ) and polynuclear ( Tong et al, 2012a ; Tong et al, 2012b ; Liu et al, 2014 ) superalkalis, aromatic superalkalis ( Sun et al, 2013 ), Zintl-ion-based superalkalis ( Giri et al, 2016 ; Sun et al, 2018b ), hyperalkalis ( Sun et al, 2016a ), alkali-metal complexes ( Tkachenko et al, 2019 ), and so on.…”
Section: Introductionmentioning
confidence: 99%
“…The theoretical work of several research groups has shown that in addition to mononuclear, there are other types of "superalkalis" such as, binuclear (M is two different electronegative atom, for example, CNLi2 or Li2CN cluster), polynuclear (M is CO3, SO3, PO4, AsO4), bimetallic (L are "mixed" alkali atoms, for example, LiNaCl cluster), and non-metallic species [17]. These clusters, their chemical bonds, which are more complex than previously described, as well as their isomers, go beyond the scope and goal of this paper and therefore are not described in detail.…”
Section: Introductionmentioning
confidence: 99%